American Justice and the First-Person Shooter. - Budra, Paul (Canadian Review of American Studies, 2004)
Formalist studies look at computer games as a new type of media experience and/or a new form of narrative. The author of this article would like to pursue this formalist line, in order to come to some conclusions about the possible ideological implications of the games. The author restricts his investigation to the type of game known as the first-person shooter. In these games, the player controls a point-of-view avatar that engages in a simulated, three-dimensional world, moving about, destroying enemies, and collecting items.